Mites (Arachnida, Acari) on Citrus sinensis L. Osbeck orange trees in the state of Amazonas, Northern Brazil - Bobot, Teiamar da Encarnação; Franklin, Elizabeth; Navia, Denise; Gasnier, Thierry Ray Jehlen; Lofego, Antonio Carlos [UNESP]; Oliveira, Byatryz Mortágua de (Instituto Nacional de Pesquisas da Amazônia, 2011)
Apesar da importância da citricultura no Brasil, pouco se conhece sobre as populações de ácaros em plantações de citros no norte do país. No município de Manaus, 12 pomares de laranja doce pulverizados foram avaliados a cada duas semanas, durante sete meses, para o registro de ácaros plantícolas e para descrever a abundância e a distribuição das espécies mais importantes. O tamanho e a idade dos pomares variaram de 3.360 a 88.0080 m² e de sete a 25 anos, respectivamente. Nos 14 períodos de coleta, folhas, galhos e frutos foram coletados de uma árvore em cada pomar. No total, 3.360 folhas, 672 galhos e 1.344 frutos foram coletados de 168 árvores. Os ácaros foram extraídos dos frutos manualmente e pelo método de lavagem nas folhas e galhos. Identificamos espécies pragas com potencial de causar danos econômicos. Registramos 14 espécies de fitófagos em quatro famílias (Eriophyidae, Tarsonemidae, Tenuipalpidae, and Tetranychidae). Brevipalpus phoenicis (Geijskes 1939) (Tenuipalpidae) e Phyllocoptruta oleivora (Ashm., 1879) (Eriophyidae), as duas espécies fitófagas mais abundantes em outras regiões, foram dominantes, mostrando que a cultura de citros local é suscetível à infestação. Registramos 11 espécies de predadores das famílias Phytoseiidae e Ascidae, compreendendo 10% da população total. Phytoseiidae foi a família mais diversa, com 10 espécies. Foram discutidos aspectos da variação temporal e utilização de hábitat das espécies mais abundantes. Estudos de longo prazo, envolvendo a aplicação de acaricidas e avaliações da comunidade de ácaros, são necessários para um melhor manejo dos pomares, levando-se em consideração a fenologia das pragas-chave.

Despite the importance of citriculture in Brazil, very little is known about mite populations in citrus crops in the Northern Region. In the municipality of Manaus, 12 sprayed sweet orange orchards were surveyed every two weeks during seven months to record mite species amount, and to describe the abundance and distribution of the most important species. The size and age of the orchards varied from 3,360 to 88,080 m² and seven to 25 years, respectively. In the fourteen sampling period, leaves, twigs and fruits were collected from 12 trees, one per orchard. In total, 3,360 leaves, 672 twigs and 1,344 fruits were sampled from 168 trees. Mites were manually extracted from the fruits, and by the washing method on leaves and twigs. We identified pests with the potential to cause economic loss. Fourteen species of phytophagous and mycophagous mites from Eriophyidae, Tarsonemidae, Tenuipalpidae, and Tetranychidae were recorded. Brevipalpus phoenicis (Geijskes 1939) and Phyllocoptruta oleivora (Ashm., 1879), the two commonest phytophagous mites in other Brazilian regions were dominant, showing that local orchards are susceptible to their infestation. Eleven predatory mites were recorded, comprising 10% of the mite population, belonging to Phytoseiidae and Ascidae. Phytoseiidae was the richest family, with ten species. The results are discussed in relation to the temporal variation aspects and habitat use of the most important species. Long-term research encompassing chemical applications followed by evaluations of the mite community are necessary for a better management of the orchards, taking into consideration the seasonal phenology of key pests.
Ácarofauna de Citrus sinensis L. Osbeck no estado do Amazonas, Brasil
Keywords: Brevipalpus; Phytophagous mites; Predatory mites; Phyllocoptruta; ácaros fitófagos; Ácaros predadores; Brevipalpus; Phyllocoptruta